2009
DOI: 10.1139/z09-088
|View full text |Cite
|
Sign up to set email alerts
|

Foods and nutritional components of diets of black bear in Rocky Mountain National Park, Colorado

Abstract: We used scat analysis to determine diets and relative nutritional values of diets for black bears (Ursus americanus Pallas, 1780) in Rocky Mountain National Park, Colorado, from 2003 to 2006, and compared foods consumed and nutritional components to identify important sources of fecal gross energy (GE), crude fat (CF), and fecal nitrogen (FN) in annual and seasonal diets. Patterns of use of food classes followed typical seasonal patterns for bears, although use of animal matter was among the highest reported (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Baldwin and Bender [51] found similar results through fecal nitrogen analysis and showed that black bears increased consumption of ants seasonally when berries and grasses were not available. This increase in fecal nitrogen [51] and δ 15 N stable isotope values (this study) could be due to a shift in increased consumption of animal matter (i.e.…”
Section: Stable Nitrogen Isotopesmentioning
confidence: 67%
“…Baldwin and Bender [51] found similar results through fecal nitrogen analysis and showed that black bears increased consumption of ants seasonally when berries and grasses were not available. This increase in fecal nitrogen [51] and δ 15 N stable isotope values (this study) could be due to a shift in increased consumption of animal matter (i.e.…”
Section: Stable Nitrogen Isotopesmentioning
confidence: 67%
“…For example, bears were observed more frequently at sites with a greater proportion of Table 3 (Baldwin 2008), with ants constituting the greatest volume of any food source consumed by bears in RMNP (Baldwin and Bender 2009a). Similarly, lodgepole pine was related to historic bear use in RMNP (1984RMNP ( -1991 L. Zeigenfuss, unpublished report).…”
Section: Discussionmentioning
confidence: 99%
“…If we consider that consuming Zostera spp. typically provides bears with relatively little energy compared to consuming animals (Baldwin and Bender, 2009), the presence of Zostera spp. in 36.36% of scats may also be due to incidental ingestion as bears forage for amphipods.…”
Section: Discussionmentioning
confidence: 99%
“…Scats are incredibly valuable resources for study that can allow researchers to gain insight into the diet, movement and range of animals (Darimont et al, 2008). Analysis of scats involves identifying food items and relating these items to diet through frequency and volume calculations (Baldwin and Bender, 2009), and inferring the diet of the animal based on faecal residue.…”
mentioning
confidence: 99%
See 1 more Smart Citation